Using The Participation Point System in Teaching Speaking Skills - Muhammad Ihsan (Universitas Syiah Kuala, 2018)
This research was aimed to investigate if there would be a significant difference in achievement between students who were taught EFL speaking skills by using the Participation Point System (PPS) technique and those who were taught by using the discussion technique at UIN Ar-Raniry Banda Aceh. It was also aimed at finding out the response of the students’ towards the use of the PPS in learning speaking skills in a conversation class at UIN Ar-Raniry Banda Aceh. The participants for this research were 30 non-English first year students in an EFL conversation class at UIN Ar-Raniry Banda Aceh. Tests and a questionnaire were used to collect the data. The findings from the research showed that the PPS can help the students improve their speaking skills more than the discussion technique in pronunciation, grammar, vocabulary, fluency, and expression. The PPS technique encourages the students to participate more in the classroom situation by asking and answering questions, expressing opinions and volunteering for classroom activities. It also creates a better teaching-learning atmosphere in the classroom.